MicroRNAs and lncRNAs—A New Layer of Myeloid-Derived Suppressor Cells Regulation - Safarzadeh, Elham; Asadzadeh, Zahra; Safaei, Sahar; Hatefi, Arash; Derakhshani, Afshin; Giovannelli, Francesco; Brunetti, Oronzo; Silvestris, Nicola; Baradaran, Behzad (Frontiers in Immunology, 2020)
Myeloid-derived suppressor cells (MDSCs) constitute an important component in regulating immune responses in several abnormal physiological conditions such as cancer. The implicated molecular mechanisms in the differentiation, expansion, and suppressive traits of MDSCs are not yet fully understood. Recent molecular investigations have provided evidence that miRNAs and long non-coding RNAs (lncRNA) are involved in modulating immune responses and the differentiation and function of MDSCs. This review provides an overview of miRNAs and lncRNAs epiregulation of MDSCs development and immunosuppressive functions in association with pathological processes focusing on cancer.